Highly efficient construction of hollow Co–Nx nanocube cage dispersion implanted with porous carbonized nanofibers for Li–O2 batteries. Issue 2 (14th December 2021) - Peng, Lichong; Sun, Yaxin; Guo, Shiquan; Li, Congju
Abstract : The integrated LOBs based on embedded or beaded Co–N x hollow cages/porous carbon nanofibers respectively exhibited significantly reduced polarization contributed by cavity utilization and long-term cyclability dedicated by the skeleton stability. Abstract : Oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) involve proton coupled electron transfer reaction (PCET), resulting in sluggish redox kinetics. At present, the development of high-efficiency bifunctional oxygen electrocatalysts is still a puzzling challenge. Herein, we propose a scalable strategy for embedding and beading ZIF-derived hollow Co–N x nanocube cage dispersion implanted with porous carbonized nanofibers (EH/PCNFs and BH/PCNFs) through electrospinning and annealing. The cobalt species prevent themselves from agglomerating during the annealing process through the "fence" effect of the non-volatile Zn species, thereby synergizing with ligand volatilization to facilitate the formation of Co–N x nanocube cages. Benefiting from the ultralong interconnected multi-layered carbon nanofiber matrix, the hollow Co–N x nanocube cages can change the charge density and electron distribution of the carbon nanofiber matrix, endowing the carbonized nanofiber carrier with special surface polarization and accelerating the electrocatalytic kinetics. Remarkably, the integrated Li–O2 batteries (LOBs) based on BH/PCNFs and EH/PCNFs electrodes exhibit significantly decreased charge/discharge polarization (0.79 V) and a long-term cyclability (147 cycles) under a cut off capacity of 500 mA h g −1 at 200 mA g −1 . This work might be beneficial for the practically viable design and manufacture of dual-function oxygen electrocatalysts.